Human-like interactions prompt people to take a robot’s perspective - Ye, Tian; Minato, Takashi; Sakai, Kurima; Sumioka, Hidenobu; Hamilton, Antonia; Ishiguro, Hiroshi (Frontiers in Psychology, 2023)
The increasing need for human-robot interaction requires not only robots to understand how humans think, but also humans to understand robots. Interestingly, little attention has been given to how humans interpret robots' behaviours. In this study, we adopted a social mental rotation task and investigated whether socially engaging behaviours could influence how people take a robot's perspectives. In a real lab, two android robots with neutral appearance sat opposite each other by a table with conflicting perspectives. Before the participant started the experiment, one of the robots behaved more interactively than the other by showing more socially engaging behaviours. Then the participant was required to identify rotated normal or mirrored digits presented inbetween the two robots. Results revealed a significant interactive effect between the digits type (normal; mirrored) and robot type (interactive; noninteractive). When digits were oriented to the interactive robot, we found a larger RT difference between normal and mirrored digits. In general, these findings suggested that robots' interactive behaviours could influence how people spontaneously consider the robot's perspective. Future studies may further consider how interactive behaviours can shape human-robot relationships and facilitate human-robot interaction.